'Demi-regs', probabilism and partly closed systems. Issue 5 (20th October 2019) - Næss, Petter
ABSTRACT: In response to an article by Steve Fleetwood on the critical realist conception of open and closed system, this paper argues that we should differentiate non-closed systems according to their degree of openness or closure, rather than applying a dichotomy between closed and open system. Societies should be conceptualized in terms of partly closed (or partly open) systems, in addition to any fully open systems that might exist in the social world. The paper furthermore argues that demi-regularities represent probability distributions existing in the real world, as distinct from occurring merely in some epistemic domain. Such partial regularities at one level of the stratified reality are necessary for the emergence of new structures at a higher stratum, for example, the social structures of a given society. Finally, implications for social science research of accepting vs. rejecting the existence of probabilities and partly closed systems in the social world are discussed.